Effect of green propolis addition to physical mechanical properties of glass ionomer cements - Valéria Barros Pereira Barbosa Troca; Karen Barros Parron Fernandes; Amélia Elena Terrile; Maria Cristina Marcucci; Flaviana Bombarda de Andrade; Linda Wang (University of São Paulo, 2011)
OBJECTIVE: This study investigated the mechanical properties of glass ionomer cements (GICs) combined with propolis as a natural antimicrobial substance. MATERIAL AND METHODS: Typifed green propolis, as an ethanolic extract (EEP) or in the lyophilized form (powder), was incorporated to specimens of Ketac Fil Plus, ChemFlex and Ketac Molar Easymix GICs. For each test, 8 specimens of each material were prepared. For water sorption and solubility tests, specimens were subjected to dehydration, hydration and redehydration cycles until a constant mass was obtained for each step. Measurements were recorded using a digital balance of 10-4 g precision. For the diametral tensile strength test, specimens were tested in a universal test machine at 0.5 mm/min crosshead speed after 24 h storage in deionized water. Data were evaluated by one-way ANOVA and Tukey's tests (p<0.05). RESULTS: The addition of propolis to GIC clearly increased water sorption compared to pure material. Solubility was material-dependent and was not clearly evident. For the diametral tensile strength test, association with propolis altered negatively only Chemfex. CONCLUSION: It may be concluded that incorporation of propolis to GICs alters some properties in a material-dependent condition.